(3cJGH aj GdbhdfLs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3GdHGH GdChd Ef CcKQ ef Jcde ef GdCWHGA hMKfG HeG dGcKQ faYg dg ai YdGL gPG GdhLY s
(3BNQgG (B:s
(3SbhW GdTghI ddWYGe hjcQg GdMdh hGdOSe ef WYGe Ch TQGH hGdMeO ddg Mb MeOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs